2019
DOI: 10.4236/ojgas.2019.96014
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Liver Fatty Acid Binding Protein (L-FABP) as a Diagnostic Marker in Non-Alcoholic Fatty Liver Disease

Abstract: Background: Non-Alcoholic Fatty Liver Disease (NAFLD) is the most common liver disease worldwide, it causes chronic hepatitis, which leads to cirrhosis and hepatocellular carcinoma. We aimed to assess the value of liver fatty acid binding protein (L-FABP) in the diagnosis of non-alcoholic fatty liver disease in comparison to ultrasonography. Patients and Methods: Ninty subjects were enrolled in this study who attended the Hepatology, Gastroenterology and Internal medicine clinics in Benha University Hospitals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 18 publications
(28 reference statements)
6
2
1
Order By: Relevance
“…Furthermore, it normalized the FABP1 levels in the NAFLD+CM group of animals. This supports previous reports of the direct relationship of the FABP1 levels and the severity of NAFLD [ 41 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, it normalized the FABP1 levels in the NAFLD+CM group of animals. This supports previous reports of the direct relationship of the FABP1 levels and the severity of NAFLD [ 41 ].…”
Section: Discussionsupporting
confidence: 93%
“…However, due to its small molecular weight (15 kDa) and its intracellular location, FABP1 is released in the serum in increased quantities in several pathological conditions involving hepatocyte injury and was reported to have a pathogenic role in NAFLD in diabetic patients [ 40 ]. Additionally, FABP1 was considered an early biomarker that determines the extent of fatty liver infiltration in NAFLD patients through increasing steatosis and subsequent activation of the hepatic stellate cells [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…While the age, gender, and height of the three groups were matched. The same outcomes were reported by Abdulaziz et al (10) . There was a notable statistical difference between the NAFLD group's weight and BMI with mean value (I) and control group (II) with relation to BMI (84.5 ± 9.5), (28.76 ± 4.3) in group І and (74.65 ± 7.44), (23.72 ± 3.04) in group II respectively.…”
Section: Discussionsupporting
confidence: 88%
“…Also, Akbal et al (7) stated that there was no age or gender difference between NAFLD patients and controls, and that as compared to the controls, the NAFLD group's BMI was greater. There was male predominance in our study in contrast to both Abdulaziz et al (10) and Akbal et al (7) ; in both groups, women outnumbered men, However, there was no difference between the groups that was statistically significant. some previous studies showed that gender is linked to NAFLD since guys are reported to be more prone to the disease, according to study.…”
Section: Discussioncontrasting
confidence: 81%
“…Furthermore, the data from cell viability, lipid content, ROS production, and gene expression analyses evidenced that the effect of the association on lipids was mediated mainly by curcumin, while the cytoprotective effect was principally ascribable to andrographolide. It has been reported that the FABP1 liver level represents a diagnostic marker in NAFLD [ 44 ], and circulating FABP1 have been found to be higher in type 2 diabetes mellitus patients with NAFLD [ 45 ]. We demonstrated that curcumin, alone and associated with andrographolide, reduces FABP1 expression, which has just been identified as a target for the medical treatment of fatty liver disease.…”
Section: Discussionmentioning
confidence: 99%